Queering Tropical Heritage: Flora and Fauna Reliefs in Karmawibhangga, Borobudur Temple, Indonesia - Rusdianto Rusdianto; Ibnu Maryanto; Aris Arif Mundayat; Hidayat Ashari; Fauziah Fauziah; Dony Satrio Wibowo; Wawan Sujarwo (eTropic: electronic journal of studies in the tropics, 2024)
Heritage inquiries into the Karmawibhangga reliefs of Borobudur Temple have not effectively revealed the degree to which flora and fauna serve as part of the network of interconnected stories depicted in the carvings of this Buddhist archaeological site in Indonesia. An exploration of the flora and fauna shown in the 160 panels of the Karmawibhangga reliefs moves beyond the accepted elucidation of the panels as mere depictions of the tenets of karma. Using approaches from intra- and extra-textuality, and tropical queer ecology to examine the flora and fauna motifs as social and environmental texts reveals the larger story within the Karmawibhangga panels. This ecological presence serves as a significant indicator of temporal, natural, and symbolically significant aspects of tropical heritage.